The effect of a carbon tax on per capita carbon dioxide emissions: evidence from Finland - Jean-David Elbaum (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
This paper is a quasi-replication of Andersson (2019). I use the synthetic control method to estimate the effect of a carbon tax starting at 1.41 per tonne of CO2 and increased through successive reforms to 20 by 2011. The results show that, one year after the intervention, the tax reduced CO2 emissions from transport by around 10% relative to the synthetic counterfactual, composed from the weighted average of OECD countries. Five years after the intervention, the effect increases to almost 20% and in 2005, the last year of the dataset, the estimated effect is of around 48%. After some robustness checks, the estimated effect is a 15% reduction in 2005. My results are consistent with Andersson (2019), who finds a 12.5% reduction at the end of his studied period. My paper contributes to the thin literature analyzing the the effect of a carbon tax ex post, providing new evidence of the effectiveness of these instruments.
Keywords: H23; Q54; Q58; 330; Solar systems; Carbon pricing; Emissions reduction; Environmental tax; Greenhouse gas emissions; Synthetic control method